Why it is not enough to have beautiful rock art sites to attract tourists? Challenges facing cultural heritage tourism in a remote area, Limpopo Province, South Africa - (:unkn) unknown (My University, 2022)
Starting from the observation that having exceptional rock art sites is not enough on its own to attract tourists, we used a case of study in the Makgabeng to analyse the challenges many remote areas face when trying to develop rock art tourism. Several initiatives to attract tourists to cultural heritage sites multiscale approach to analyse factors that impact a given place, and the interactive and evolving dynamics linking these factors on different spatial levels. This type of analysis provides a synoptic and holistic assessment of the challenges facing tourist development projects in remote areas.
Keywords: African Research